Mutu Guru di Negara Malaysia, Singapura, Thailand dan Finlandia - Nisa Nurasiah (Edulead : Journal of Education Management, 2022)
Education is a very significant thing in the life of a nation. This makes a nation to increasingly try to advance the quality of education in their respective countries, as well as the countries of Singapore, Malaysia, Thailand and Finland. The purpose of this study is to analyze the extent of efforts to develop teacher quality in these four countries. The type of research used is a literature study. The data used comes from textbooks, journals, scientific articles, literature reviews which contain the concepts studied. The research results of this article contain the following points; (1) Singapore pays full attention to human resources through a number of education reform programs such as thinking school, learning nation; teach less, learn more, and school excellent models which have proven to be effective in creating quality human resources. (2) The majority of school principals in Malaysia have a sporty spirit and have a positive influence on the intrinsic growth of teachers, especially their motivation and satisfaction of their interest in work (3) Improving the quality of Thai teachers is carried out with a 5-year teacher education program with scholarships. The minimum teacher qualification must be a bachelor's degree. Teacher development is carried out in various forms, ranging from training and advanced studies to masters and even doctorates. (4) Finland has an accountability-based teacher evaluation investigative model to assess teacher effectiveness.